2019
DOI: 10.1371/journal.pone.0210788
|View full text |Cite
|
Sign up to set email alerts
|

The pregnancy outcomes of patients with rudimentary uterine horn: A 30-year experience

Abstract: ObjectivesTo evaluate the presentation, assessment, treatment, and pregnancy outcomes of 22 women with a rudimentary uterine horn.MethodsWe reviewed the data regarding the outcomes of patients with a rudimentary horn pregnancy (RHP) who were managed at Peking Union Medical College Hospital over the last 30 years. Twenty-two pregnant patients with a rudimentary horn have been treated at our institute over the last 30 years. All patients with RHP were divided into two groups: Type A (n = 4), a rudimentary horn w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…Studies in the literature showed that rupture was significantly higher in communicant rudimentary horn pregnancies. Rupture was observed in communicant 60% and non-communicants 17.6% [15]. In our study, one patient with communicating rudimentary horn pregnancy was admitted to our clinic with rupture (100%).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Studies in the literature showed that rupture was significantly higher in communicant rudimentary horn pregnancies. Rupture was observed in communicant 60% and non-communicants 17.6% [15]. In our study, one patient with communicating rudimentary horn pregnancy was admitted to our clinic with rupture (100%).…”
Section: Discussionmentioning
confidence: 53%
“…Following the confirmation of RHP and excision of the horn, termination of pregnancy must be considered and performed, if necessary [15]. In the present study, 2 (33.3%) of 6 patients got a diagnosis of RHP during routine pregnancy follow-up visits after 2012.…”
Section: Discussionmentioning
confidence: 64%
“…When a rudimentary horn is present, it is the noncavitary type in 33% of cases, the cavitary but noncommunicating type in 22% of cases, and the cavitary and communicating type in 10% of cases [8].…”
Section: Discussionmentioning
confidence: 99%
“…Most cases of rudimentary horn pregnancy (RHP) provide a diagnostic challenge and are diagnosed after rupture, which leads to emergency surgery, blood transfusions, and increased morbidity [8].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of rudimentary horn pregnancy is very low (1 in 76 000–150 000 pregnancies) [1,[3], [4], [5], [6],9,12,13,18]. It mainly occurs in a non-communicating rudimentary horn by transperitoneal migration of sperm or fertilized ovum [[3], [4], [5], [6],9,11,12].…”
Section: Introductionmentioning
confidence: 99%